Vpliv projekta Evropska prestolnica kulture 2012 na turistični obisk v Mariboru - Horvat, Uroš (Revija za geografijo, 2013)
The article discusses the impact of the international cultural project European Capital of Culture Maribor 2012 on a tourist visit in the city. The author analyzes in particular the data of the stationary tourist visits (number of tourists and overnight stays, share of overnight stays by country, the average length of stay of tourists, the seasonality of tourist visit) in 2012, and compared them with the years prior to the implementation of the project, and the year 2013. Where possible, he uses a comparison with the data in the city of Pecs (Hungary), which wore the title of ECoC in 2010. ECoC Maribor 2012 was the biggest and most recognizable cultural project in the history of Slovenia. In addition to the direct effect on cultural activity and its development, the project has had a major impact also on the promotion of Maribor and partner towns, as well as Slovenia in general. It had also significant positive effects on the local economy; in Maribor in 2012 were registered about 19% more tourist arrivals and 17% more overnight stays than the year before, and the tourist visit remained in 2013 almost at the same level.
Keywords: 2012; culture; Evropska prestolnica kulture; kultura; kulturne prireditve; Maribor; tourism; turizem